Transportation Indicators for Roads Network in Ramadi City - Khudier, Rafal; Mahmood, Thaer; Awad, Hamid (Iraqi Journal of Civil Engineering, 2024)
One of the most important aspects of the developing any area is creating a viable road network and defining the relationship between landscape use and road networks. Proper communication and direction are essential to the proper construction of any network. In addition to providing chances for production and consumption, resource extraction, and social cohabitation, the road network also functions as a hub for these activities. As a consequence, this contributes to the development of cities and the improvement of the level of living. However, Ramadi’s road network has not received much attention and evaluation. To identify Ramadi road network transportation indicators, the researchers used geospatial information systems. Connectivity was assessed using the alpha, beta, gamma, and eta indices to describe and analyse the network. The data was collected in the first quarter of 2024. The Alpha, the beta, the gamma, and the eta indexes show weak Al-Ramadi road network connections. Indexes are 0.197, 1.26, 0.43, and 0.82. The research indicates a loss in network connectivity in the study region, necessitating the prioritization of new the roads and a city plan to mitigate network shortages.